The effects of size on local banks' funding costs - Oliver Vins; Thomas Bloch (Johann Wolfgang Goethe-Universität Frankfurt am Main, Fachbereich Wirtschaftswissenschaften, 2008)
Motivated by the recent discussion of the declining importance of deposits as banks' major source of funding we investigate which factors determine funding costs at local banks. Using a panel data set of more than 800 German local savings and cooperative banks for the period from 1998 to 2004 we show that funding costs are not only driven by the relative share of comparatively cheap deposits of bank's liabilities but among other factors especially by the size of the bank. In our empirical analysis we find strong and robust evidence that, ceteris paribus, smaller banks exhibit lower funding costs than larger banks suggesting that small banks are able to attract deposits more cheaply than their larger counterparts. We argue that this is the case because smaller banks interact more personally with customers, operate in customers' geographic proximity and have longer and stronger relationships than larger banks and, hence, are able to charge higher prices for their services. Our finding of a strong influence of bank size on funding costs is also in an in international context of great interest as mergers among small local banks - the key driver of bank growth - are a recent phenomenon not only in European banking that is expected to continue in the future. At the same time, net interest income remains by far the most important source of revenue for most local banks, accounting for approximately 70% of total operating revenues in the case of German local banks. The influence of size on funding costs is of strong economic relevance: our results suggest that an increase in size by 50%, for example, from EUR 500 million in total assets to EUR 750 million (exemplary for M&A transactions among local banks) increases funding costs, ceteris paribus, by approximately 18 basis points which relates to approx. 7% of banks' average net interest margin.
Keywords: G21; G34; L25; C23; 330; Regional banks; bank funding; mergers & acquisitions; Sparkasse; Kreditgenossenschaft; Regionalbank; Einlagengeschäft; Kapitalkosten; Übernahme; Fusion; Deutschland